2019
DOI: 10.1016/s2352-3018(18)30362-x
|View full text |Cite
|
Sign up to set email alerts
|

Slow-release naltrexone implant versus oral naltrexone for improving treatment outcomes in people with HIV who are addicted to opioids: a double-blind, placebo-controlled, randomised trial

Abstract: Background: Untreated opioid addiction in persons with HIV is associated with poor outcome. Slow release, long-acting, implantable naltrexone may improve outcomes. Methods: We conducted a 48-week outcome study beween July 2011 and April 2015 of opioid addicted males and females starting antiretroviral treatment (ART) for HIV whose viral loadwas ≥1000 copies per mL and were seeking treatment at HIV and Narcology programs in St. Petersburg and the surrounding Leningrad Region, Russian Federation. We stratified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This finding is in line with a few previous reports from Iran [58] and other countries [59]. However, another study reported otherwise [60].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with a few previous reports from Iran [58] and other countries [59]. However, another study reported otherwise [60].…”
Section: Discussionsupporting
confidence: 93%
“…In a trial in Russia, people with OUD and untreated HIV were randomized to receive long‐acting naltrexone implants or daily oral naltrexone dosing. At 24 weeks, 38% of those assigned to long‐acting naltrexone and 35% of those assigned to oral naltrexone achieved an HIV viral load < 400 copies/ml [15]. HIV viral suppression rates of 52.7% at 24 weeks among those randomized to XR‐NTX in the CHOICES trial exceeds viral suppression observed in these prior studies, as well as a systematic review of 32 mainly observational studies that reported a 45% increase in HIV viral suppression attributed to opioid agonist treatment [4].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that initiating XR‐NTX in a non‐addiction specialty outpatient setting facilitates HIV viral suppression on a level comparable to initiating opioid agonist treatment. While OUD treatment adherence most probably mediates the effect of XR‐NTX on HIV viral suppression [15], XR‐NTX may also mitigate risky decision‐making and improve treatment adherence through central effects on the reward pathway [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral treatment of naltrexone for opioid dependence is ineffective due to poor treatment adherence ( Minozzi et al, 2011 ). Naltrexone implant, on the other hand, has produced some positive results in the treatment of opioid or polydrug abuse ( Kelty et al, 2019 ; Krupitsky et al, 2019 ). Nevertheless, the clinical efficacy of the implant in the long-term has not been reported and the potential opioid overdose associated with naltrexone implant has not been sufficiently explored ( Saucier et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%